Pycnodysostosis associated with bilateral congenital pseudarthrosis of the clavicle - Karakurt, L; Yilmaz, E; Belhan, O; Serin, E (Springer-Verlag, 2003)
We report the case of a 22-year-old woman with pycnodysostosis associated with bilateral congenital pseudarthrosis of the clavicle. The patient was first seen at the age of 19 years and had no symptoms during the 3-year follow-up period. The diagnosis of pycnodysostosis was made by typical clinical and radiological findings. Bilateral painless mid-clavicular mass and plain radiograms confirmed the diagnosis of bilateral congenital pseudarthrosis of the clavicle. Surgery was not performed for pseudarthrosis of the clavicles, just observation was preferred.
Keywords: pycnodysostosis; bilateral congenital pseudarthrosis of the clavicle